UJI MORTALITAS KECOA AMERIKA (Periplaneta americana) MENGGUNAKAN EKSTRAK KULIT DURIAN (Durio zibethinus Murr) - Wahyuni, Denai; Muktitama, Risa Etika (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2019)
Cockroaches can transmit disease to humans both mechanically and biologically, among others, dysentery, diarrhea, cholera, hepatitis A virus and polio in children. One effort that can be done in reducing the American cockroach without using synthetic insecticides is by using durian leaf extract (DuriozibethinusMurr). The purpose of this study was to determine the content of secondary metabolite compounds present in the skin of durian, determining the mortality of the American cockroaches and determining the LC50 value. This research was conducted by using experimental laboratory method in vivo. Durian leather extracts were made in various concentrations of 5%, 10%, 20%, and 30%, then put the American cockroach into the test box and observed for 3 hours. Based on the research, durian leaf extract contains flavonoid compounds, saponins, tannins and alkaloids. Percentage of mortality of American cockroaches. at concentrations of 5%, 10%, 20% and 30% respectively ie 11.11%, 22.22%, 38.88% and 61.11% with LC50 values ​​of 2,63x105 ppm. It can be concluded that durian skin extract is capable of killing American cockroaches characterized by the percentage of death of American cockroaches.